Force sensing resistors for monitoring proprioception response in rehabilitation routines - Gopalai, Alpha; Senananayake, A. (IEEE, 2012)
During rehabilitation routines for postural control, clinician use proprioception training involving wobble boards to help strengthen the proprioception. Wobble board routines are carried out for at least six weeks, subjects are required to perform certain motions on the boards which are targeted to improve proprioception. Subjects perform this tasks without (or with minimal) real-time feedback. A real-time system to monitor proprioception training, using a wobble board, was designed and tested. This work presents a force sensing platform, equipped with soft-computing methods to measure effects of destabilizing postural perturbations. Experiments were conducted to verify the system's ability to monitor and gauge subject's postural control via proprioception. The experimental set-up was observed at a frequency of three times a week for a duration of six weeks. Fuzzy clustering and area of sway analysis was used to determine the effects of training on subjects' postural control in Eyes Open (EO) and Eyes Close (EC) conditions. All data was tabulated and compared using one-way ANOVA to determine its statistical significance, with a false rejection ratio α = 0.05. The results of the experiment supported the suitability of the system for clinical applications pertaining to postural control improvements.